Style panorama of ukrainian button accordion music of the end of the XX - the beginning of the XXI centuries introduction - Stashevskyi, Andrii (My University, 2019)
Modern button accordion music, which has a wide range of different genres and forms of music (created, including by Ukrainian composers), clearly shows a unique complex of artistic and expressive means, capable of accurately and convincingly embodies the highly artistic tasks of composer and performer creative work that in its turn justly confirms the high positions and the great potential of this kind of music instrumental art in the focus of the artistic processes today.
Keywords: музика українська, Ukrainian music